PERTANGGUNGJAWABAN PIDANA PELAKU TINDAK PIDANA PENGGELAPAN DALAM JABATAN DARIPERSPEKTIF HUKUM PIDANA INDONESIA - Akbar, Muhammad Syarif Hidayatullah; Chandra, Tofik Yanuar; Ismed, Mohamad (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Indonesia, as a state based on the rule of law as stipulated in Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia, obliges every citizen to uphold the law without exception. In the context of criminal law, the principle of legality as stated in Article 1 paragraph (1) of the Indonesian Criminal Code (KUHP) establishes that an act can only be punished if it is regulated by law. One of the most common criminal offenses is embezzlement in office as regulated in Article 374 of the KUHP, which constitutes an aggravated form of ordinary embezzlement under Article 372 of the KUHP. This offense is often committed by individuals holding positions or employment relations, both in the private and public sectors, who abuse their authority to unlawfully control goods or money. This research aims to analyze the criminal act of embezzlement in office and the criminal liability of its perpetrators from the perspective of Indonesian criminal law. The study employs a normative juridical research method with statutory, case, conceptual, and analytical approaches. Data were obtained through library research consisting of primary, secondary, and tertiary legal materials, and analyzed using grammatical and systematic interpretation techniques. The findings show that the application of Article 374 of the KUHP in practice often encounters sentencing disparities, where court verdicts tend to be lighter than the prosecutors’ demands. This disparity is evident in several court decisions examined, in which sentence reductions were based on subjective considerations such as the defendant’s cooperative attitude, restitution of losses, and social background. Normatively, the criminal liability of perpetrators of embezzlement in office must be based on the principle of legality, conformity with statutory elements, and evidentiary processes in court. However, in practice, there is a gap between the theoretical framework of criminal law and its implementation, indicating the need for consistent law enforcement to ensure legal certainty and justice